The Structure of Public Policy Models Mediated by Public Services on the Performance of Makassar City Government Apparatus - Rusdin Nawi (IHSA Institute, 2022)
The model structure that is in the spotlight in administrative actualization is political policy, the social and economic environment, as agency progress and a fundamental step in the era of society 5.0. The research approach uses exploratory, ex post facto and causal studies. There are two types of data, namely quantitative data and qualitative data. Sources of data in this study consisted of primary and secondary data. Data collection techniques are observation, questionnaires, interviews and documentation. The population is 11,067 civil servants of Makassar City Government. The sample using the 0.10% Slovin formula was obtained as many as 99 apparatus respondents. Data analysis techniques are descriptive statistical analysis techniques and Structural Equation Modeling (SEM) analysis. The results show that political policies based on trust, conflict, power, strategy and paradigms have an effect on public services and apparatus performance. Social environmental policies in the form of facilities, competition, security, comfort and communication affect public services and apparatus performance. Economic policies seen from income, equity, unemployment, transactional and budgeting affect public services and apparatus performance. Public services in the form of simplicity, fairness, transparency and economy affect the performance of the apparatus in terms of quantity, quality, efficiency, effectiveness and loyalty of each apparatus. Likewise, political policies, the social environment and the economy indirectly have a significant effect on the performance of the apparatus through public services from the government apparatus, which means that the latent structure of public policies contributes to influencing the improvement of the performance of the apparatus through the services applied to the public.